Soil and crop responses following application of biosolids-derived organomineral fertilisers to ryegrass (Lolium perenne L.) grown in pots - Antille, Diogenes Luis; Sakrabani, Ruben; Godwin, R. (American Society of Agricultural and Biological Engineers, 2014)
Biosolids-derived organomineral fertilisers (OMF) were produced using a novel technique reported in earlier studies. This technique enables addition of N and potash to biosolids granules to form a balanced NPK fertiliser. Two fertiliser products; OMF10 (10:4:4) and OMF15 (15:4:4), were formulated and tested in a glasshouse facility on pot-grown ryegrass in comparison with urea and biosolids granules at N application rates ranging from 0 to 300 kg ha-1. The aim of this research was to contribute to the understanding of nutrients management and dynamics in grass crops fertilised with OMF. The study focused upon dry matter yield (DMY) and crop responses to applied fertiliser, nitrogen use efficiency (NUE) and fertilisers’ effect on soil fertility. Results indicated that ryegrass responds linearly to application of OMF increasing DMY by about 2% to 27% compared with biosolids but to a lesser extent than urea (range: 17% to 55%). NUE was related to the concentration of readily available N in the fertiliser; urea and OMF showed significantly greater (P<0.05) N recoveries than biosolids (26% to 75%, and 19% to 29%, respectively). Total nitrogen in soil and SOM increased (P<0.05) depending on the concentration of organic-N in the fertiliser applied. DMY was lower but more sustained overtime in biosolids-treated pots. OMF application did not result in significant changes in soil extractable-P levels whereas for urea, it decreased significantly while it showed a significant increase in biosolids-treated pots, where soil-P Index changed from 5 to 6. In OMF-treated soil, soil P Index remained close to constant overtime thereby supporting the purpose of the formulations tested.
Keywords: Biosolids granules; Dry matter yield; Organomineral fertilisers (OMF); Ryegrass; Soil nutrient dynamics; Soil P Index